Double Jahn–Teller Distortion in AuGe Complexes Leading to a Dual Blue–Orange Emission. Issue 2 (17th September 2015) - Bojan, R. Vilma; López‐de‐Luzuriaga, José M.; Monge, Miguel; Olmos, M. Elena; Echeverría, Raquel; Lehtonen, Olli; Sundholm, Dage
Abstract: The tetrahedral Au I complexes [Au(GeCl3 )L3 ] (L=PMe3 (1 ), PMe2 Ph (2 ), PMePh2 (3 ), PPh3 (4 )) were synthesized by in situ treatment of the [Au(GeCl3 )(tht)] complex with three equivalents of the corresponding tertiary phosphine. The crystal structures of complexes 1 and3 have been determined through X‐ray diffraction studies and show [GeCl3 ] − fragments bonded to the corresponding [Au(PR3 )3 ] + units through covalent bonds, leading to a tetrahedral coordination environment for gold. Complexes 3 and4 show dual phosphorescence in the solid state at 77 K and, in the case of complex 4, an interesting room‐temperature mechanochromism effect is observed. Correlated MP2, SCS‐MP2, SCS‐CC2, and ONIOM MP2/UFF calculations suggest the existence of two largely distorted and thermally connected triplet excited states (T1 and T2 ) for a model system of complex 4 . The AuP3 + moiety can be distorted in two different planes leading to the two triplet excited states T1 and T2, leaving the GeCl3 − unit almost unaltered. The emissions of these phosphorescent Au I Ge II complexes is mainly ascribed to a metal (gold)‐centered ( 3 MC) transition with some contribution from the [GeCl3 ] − fragments. Abstract : Team colors : The inorganometallic Au I complexes [Au(GeCl3 )L3 ] (L=PMe3 (1 ), PMe2 Ph (2 ), PMePh2 (3 ), PPh3 (4 )) have been synthesized. Complexes 3 and4 display dual phosphorescence in the solid state. Ab initio calculations show that the existence of two different triplet excited states, T1 and T2, is related to this phosphorescent behavior. A double Jahn–Teller effect for each triplet‐state structure is described.